Specific Identities Involving Prime Ideals with Generalized $P$-derivations (European Journal of Pure and Applied Mathematics, 2025)
In this article, we will investigate the commutativity of the factor ring $\Re/P$, where $P$ is a prime ideal of any ring $\Re$. This investigation will be carried out using generalized $P$-derivations $\mho$ and $\amalg$ associated with $P$-derivations $χ$ and $\propto$, respectively, that satisfy specific functional identities linking $\Re$ to $P$. Moreover, we will discuss some related results. Finally, to reinforce the importance of our assumption regarding the primeness of $P$, we will provide some examples.
Keywords: Generalized $P$-derivation; integral domain; prime ideal; factor ring